PROJECTION OF THE INFLATION RATE IN PANGKALPINANG CITY USING THE AUTOREGRESSIVE MOVING AVERAGE (ARMA) - Dalimunthe, Desy Yuliana; Sulistiana, Ineu; Saputra, Darman; Aldila, Herman; Pririzki, Sisilia Jesika (PATTIMURA UNIVERSITY, 2023)
Inflation is one of the variables in the macro economy that can affect people's welfare and is defined as a complex phenomenon due to general and continuous price increases. This study aims to project the inflation rate in Pangkalpinang City, Bangka Belitung Islands Province in the period of October, November, and December of 2022. The historical inflation data used in this study is presented in a monthly period from January 2004 ends in October 2022 and January 2023 obtained from the publication of the Central Statistics Agency (BPS) of the Bangka Belitung Islands Province. The process projection is done using the Autoregressive Integrated Moving Average (ARIMA) model after passing the model fitting process first. The projection results obtained using historical inflation data show that the ARIMA model that is suitable for the projection process is the ARMA model (4,4) with the best RMSE value of 1.21 and MAE of 0.89. Through the results of this projection, it is also obtained that the percentage value of the inflation rate in Pangkalpinang City has decreased by 0.03% in the period of October 2022 and has increased in the period of November by 0.05%, then the inflation rate in Pangkalpinang City will again decline in the period of December 2022. by 0.3% and an increase of 0.33% in January 2023.